PENGEMBANGAN PENUNTUN PRAKTIKUM INDIKATOR ASAM BASA BERBASIS KONTEN LOKAL KALIMANTAN BARAT - Ria Tri Wulandari; Dini Hadiarti; Dedeh Kurniasih; Rizmahardian Ashari Kurniawan (Jurnal Ilmiah Ar-Razi, 2019)
Acid-base is taught at SMA Negeri 1 Nanga Pinoh by using practical methods. Therefore, in order to deliver the material effectively and ideally, the proper guidebook is absolutely required. This study aimed to develop a valid, practical, and effective practical guide for acid-base material based on the local content of West Kalimantan. Using an R & D model of Borg and Gall, seven out of eleven stages of material design were employed. They were research and data collection, planning, draft development, initial product trial, initial product revision, main field trial, and revision of operational products.The data collection technique used were observation, questionnaire, and measurement. The instruments were observation and questionnaire sheet, and posttest questions. The study was obtained: (1) the coefficient of validity from the assessment of media, material and language experts were 1.00; (2) the response value on the initial field trial was 88.8%, and the response value on the main field trial was 89.16%; and (3)The student learning outcomes after taught using this practical guide were sharply improved by 97%. In conclusion, the practical guide for acid-base material based on the local content of West Kalimantan is effective to be used by the students of SMA Negeri I Nanga Pinoh.